Intrarenal delivery of bFGF-loaded liposome under guiding of ultrasound-targeted microbubble destruction prevent diabetic nephropathy through inhibition of inflammation - Sheng, Wen-Shuang; Xu, He-Lin; Zheng, Lei; Zhuang, Yuan-Di; Jiao, Li-Zhuo; Zhou, Jia-Feng; ZhuGe, De-Li; Chi, Ting-Ting; Zhao, Ying-Zheng; Lan, Li (Artificial cells, nanomedicine, and biotechnology, 2018)
Basic fibroblast growth factor (bFGF) has shown great therapeutic effects for diabetic nephropathy (DN). However, its clinical applications are limited due to its short half-life, low stability and poor penetration. Herein, a bFGF-loaded liposome (bFGF-lip) was constructed and combined with ultrasound-targeted microbubble destruction (UTMD) to overcome these drawbacks. bFGF-lip exhibited spherical morphology with a diameter of 171.1 ± 14.2 nm and a negative zeta potential of -5.15 ± 2.08 mV, exhibiting a sustained-release profile of bFGF. DN rat models were successfully induced by streptozotocin. After treatment with bFGF-lip + UTMD, the concentration of bFGF in kidney of DN rats was significantly enhanced in comparison with free bFGF treatment. Additionally, the morphology and the function of the kidneys were obviously recovered after bFGF-lip + UTMD treatment as shown by ultrasonography and histological analyse. The molecular mechanism was associated with the inhibition of renal inflammation. After treatment with bFGF-lip + UTMD, the activation of NF-κB was obviously reduced in the renal tissues, and downstream inflammatory mediators including TGF-β1, MCP-1, IL-6 and IL-1β were also down regulated. In addition, inflammation-induced cellular apoptosis of renal tubular cells was also significantly inhibited by detecting Bax, caspase-3 and Bcl-2. Therefore, bFGF-lip in combination with UTMD might be a potential strategy to reverse the progression of early DN.